Tendências de incidência e de mortalidade por câncer no município de Aracaju, Sergipe - Lima, Carlos Anselmo (2013)
Population-based studies have been used to provide hypothesis about cancer etiology as well as in the identification of risk factors, and data have been obtained through population-based cancer registry databases. The aim of the study has been to describe time trends in cancer incidence and mortality in the population of Aracaju, Sergipe from 1996 to 2007. The methods used have consisted of an ecological study of time trends using data from the Population-based Cancer Registry of Aracaju and from The Mortality Database for the State of Sergipe. Incidence and mortality rates have then been calculated, based on official population counts and estimates. Time trends have been calculated by the Joinpoint Regression Program, National Cancer Institute, USA. The results showed rising incidence and mortality rates during the period of study. Cancer sites showing the highest age-standardized rates were; prostate, lungs, oral cavity, stomach, and colorectum in males; and breast, cervix, thyroid, colorectum, and uterine body in females. The sites exhibiting the highest age-standardized mortality rates were: prostate, lungs, stomach, oral cavity, and liver in males; and breast, lungs, cervix, uterine body, and colorectum in females. Incidence trends showed a rising pattern in males, but for females, only for crude rates until the year 2001. Mortality trends showed a ring pattern only in males. The features observed in the population studied have shown similarities with the ones observed in highincome areas, but conversely have shown, considering some cancer sites, such as cervix and oral cavity, the same pattern observed in low-income areas.